Analysis of Social Change: The Transformation of Traditional Traders at Pasar Raya Padang in the Digital Economy Era - Hanafi Saputra; Ahmad Hidayah; Yuhelna Yuhelna; Isnaini Isnaini; Anisatun Indriyani (LPPM Universitas PGRI Sumatera Barat, 2025)
The rapid development of the digital economy has significantly transformed trade structures in Indonesia, including traditional markets that have long been the backbone of community-based economic activities. This study aims to analyze the changes and impacts experienced by traditional traders in Pasar Raya Padang in the digital economy era. The research employed a qualitative approach with a descriptive-analytical design. Data were collected through in-depth interviews, participatory observations, and documentation, and analyzed using thematic analysis with source and method triangulation to ensure validity. The findings reveal that traditional traders in Pasar Raya Padang are undergoing social changes marked by adaptation gaps to digital technology. Younger traders tend to adopt social media platforms and electronic payment systems to expand their market reach, while older traders face difficulties due to limited digital literacy. The economic impact is ambivalent: adaptive traders experience increased income, while non-adaptive traders face declining sales. Socially, face-to-face interactions have decreased, yet new, more transactional relationships have emerged in digital spaces. This study concludes that Pasar Raya Padang represents a dynamic interaction between tradition and modernity, resulting in a hybrid form of trade. The findings highlight the importance of empowering traditional traders through digital literacy programs, supportive policies, and community collaboration to maintain the competitiveness of traditional markets in the digital era.